2018
DOI: 10.1002/ana.25204
|View full text |Cite
|
Sign up to set email alerts
|

Recessive mutations in VPS13D cause childhood onset movement disorders

Abstract: VPS13 protein family members VPS13A through VPS13C have been associated with various recessive movement disorders. We describe the first disease association of rare recessive VPS13D variants including frameshift, missense, and partial duplication mutations with a novel complex, hyperkinetic neurological disorder. The clinical features include developmental delay, a childhood onset movement disorder (chorea, dystonia, or tremor), and progressive spastic ataxia or paraparesis. Characteristic brain magnetic reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
129
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(146 citation statements)
references
References 23 publications
6
129
2
3
Order By: Relevance
“…To date, HSP has been reported in only one patient (Gautheir et al, ). According to earlier reports (Gautheir et al, ; Seong et al, ), 19 patients exhibited cerebellar ataxia (79%; 15/19), movement disorders (dystonia, chorea, and tremor) (37%; 7/19), cognitive impairment (42%; 8/19), and spastic paraplegia (0.5%; 1/19). Our four patients exhibited spastic paraplegia (100%; 4/4), cerebellar ataxia (25%; 1/4), movement disorders (25%; 1/4), and no cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, HSP has been reported in only one patient (Gautheir et al, ). According to earlier reports (Gautheir et al, ; Seong et al, ), 19 patients exhibited cerebellar ataxia (79%; 15/19), movement disorders (dystonia, chorea, and tremor) (37%; 7/19), cognitive impairment (42%; 8/19), and spastic paraplegia (0.5%; 1/19). Our four patients exhibited spastic paraplegia (100%; 4/4), cerebellar ataxia (25%; 1/4), movement disorders (25%; 1/4), and no cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Only the CADD score, which was 22, indicated disease causing. To date, 23 mutations in the VPS13D have been described (Gautheir et al, ; Seong et al, ). Earlier studies showed 11 compound heterozygous mutations and one homozygous mutation (Gautheir et al, ; Seong et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Separately, in this same issue, Gauthier et al report a family with 2 patients with spastic ataxia, chorea, and dystonia also harboring variants in VPS13D . Another 5 cases from 4 additional families were located at collaborative sites, also utilizing contributions from GeneMatcher . In this cohort, all patients showed early onset before age 12 years, developmental delay, intellectual disability, axial hypotonia, and chorea, eventually progressing to spastic ataxia and dystonia in adulthood .…”
mentioning
confidence: 99%
“…Further complicating the phenotypic spectrum, 1 family presented with early tremor progressing to dystonia, spasticity, and mild ataxia as adults. MRI of the brains of the cohort showed T2/fluid‐attenuated inversion recovery hyperintensities either in a pattern restricted to the putamen and caudate, or more diffusely involving the white matter, reminiscent of patterns described in Leigh syndrome …”
mentioning
confidence: 99%
See 1 more Smart Citation